DEVELOPMENT ON ENHANCING MOTIVATION WORK PERFORMANCE OF THE TEACHER AT YASOTHON PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Saimek, Neungruthai; Chittranum, Thatchai (Journal of MCU Nakhondhat, 2020)
The purposes of this research were 1) to study current conditions, desirable conditions, and requirement to enhance motivation work performance of the teacher 2) to develop guidelines of enhance motivation work performance of the teacher. The research had been conducting for 2 phases. The first phase was the study of current conditions, desirable conditions, and requirement to enhance motivation work performance of the teacher by sampling group which consisted of the teachers for 296 persons. The current conditions instrumentation of the study was questionnaire which had 0.38 – 0.88 discrimination value and 0.96 reliability value of all the copy. The desirable conditions instrumentation of the study was questionnaire which had 0.32 – 0.88 discrimination value and 0.95 reliability value of all the copy. The numeral data in this research was analyzed by percent, mean, standard deviation of the mean. The second phase was to develop the development guideline of enhance motivation work performance of the teacher by sampling group which consisted of the directors and teachers for 19 persons. The instrumentation of the study was structured interview form by studying best well – known arrangement schools. The interview data in this research was analyzed by descriptive analysis. The development guideline was evaluated by 5 specialists. The data were collected by using evaluation form. The numeral data in evaluation form was analyzed by percent, mean, standard deviation of the mean. The research found that: 1) The current conditions, desirable conditions, and requirement to enhance motivation work performance of the teacher were at a high level. 2) Development guidelines of enhance motivation work performance of the teacher consisted of 5 aspects which were 1) Achievement) 2) Interpersonal Relations with Peers 3) Interpersonal Relations with Supervision 4) Recognition 5) Compensations and Welfare. The Evolution form specialist also showed that the suitability of the guideline for developing was in the highest level and the possibility is in high level.